Does subsidizing investments in energy efficiency reduce energy consumption? Evidence from Germany - Caroline Dieckhoener (Institute of Energy Economics at the University of Cologne (EWI), 2012)
Improving energy efficiency is one of the three pillars of the European energy and climate targets for 2020 and has led to the introduction of several policy measures to promote energy efficiency. The paper analyzes the effectiveness of subsidies in increasing energy efficiency in residential dwellings. An empirical analysis is conducted in which the effectiveness of subsidies on the number of dwelling modernizations is investigated. Next, the impact of renovations on energy consumption is analyzed using a differences-indifferences-in-differences approach for modernizations made in given subsidy program periods, as well as for ownership status and household types for more than 5000 German households between 1992 and 2010. By controlling for socio-economic status, dwelling characteristics and macro-indicators, it becomes apparent that homeowners invest signi ficantly more and have significantly lower heating expenditures than their tenant counterparts. Thus, the landlord-tenant problem tends to broaden the energy efficiency gap. It is also found that the number of modernizations made by landlords does not increase with higher subsidies. However, the renovations made during the subsidy periods decrease the heating consumption of tenants. Given the conditions that homeowners already invest more in energy efficiency, they increase modernizations only slightly with increasing subsides. However, these modernizations during subsidy periods do not further decrease homeowners' energy consumption. Thus, the large part of the overall subsidies received by homeowners can be identified as windfall prots.
Keywords: D12; Q51; R21; 330; Household behavior; econometric analysis; energy efficiency; demand modelling